FAKTOR YANG BERHUBUNGAN DENGAN KELENGKAPAN IMUNISASI DASAR DI PUSKESMAS RAWAT INAP SIMPANG TIGA - RIKA ISTAWATI; Penti Dora Yanti; Vidya Anggraini (Jurnal Ilmu Kebidanan, 2019)
ABSTRACT Immunization is one form of health intervention that is very effective in efforts to reduce infant and under-five mortality. Based on the Results of Monthly Reports on Routine Immunization of Pekanbaru City Health Center Infants, the Simpang Tiga Inpatient Health Center has the lowest immunization coverage from 20 puskesmas. This type of research is quantitative analytic with cross sectional approach. The population in this study were mothers who had infants aged 9 months to 2 years in the Simpang Tiga Inpatient Health Center with a sample of 71 respondents. In this study the technique used was accidental sampling. The instrument used in this study was a questionnaire. From the results of the study it was found that the variables related to the completeness of basic immunization were the level of knowledge of the mother (pvalue = 0,000). Whereas the variables not related to the completeness of basic immunization are the mother's education level (pvalue = 0.321), and family support (pvalue = 0.619)